Β3-Adrenoceptor Agonist for the Treatment of Bladder Dysfunction in Children: A Systematic Review and Meta-Analysis. Issue 3 (1st March 2022) - Kim, Jin K.; De Jesus, Mark Jason; Lee, Min Joon; Dos Santos, Joana; Dy, Jun S.; Ming, Jessica M.; Rickard, Mandy; Lorenzo, Armando J.; Chua, Michael E.
Abstract : Purpose: ß3-adrenergic receptor agonists (ß3 agonists) have been used in treatment of overactive bladder (OAB) and neurogenic detrusor overactivity (NDO) in adults. However, their use in children has only recently been approved by the U.S. Food and Drug Administration for patients with NDO. As in adults, the role of ß3 agonists in children may include conditions such as OAB. This systematic review and meta-analysis aims to understand the intended use, efficacy and safety of ß3 agonists in the pediatric population. Materials and Methods: A literature search was performed in February 2021 across MEDLINE®, Embase®, Scopus®, the Cochrane Library and ClinicalTrials.gov . No language restrictions were placed. All records describing the clinical use of ß3 agonists in pediatric patients (<18 years of age) were included, regardless of the methodological design or outcomes assessed. The identified records were screened by 2 independent authors. The reporting was compliant with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement. Data extraction was performed by 2 independent reviewers, blinded to each other's extractions. The data were pooled using the fixed effects model. Results: Of 367 records identified, 8 studies were included in the review (3 prospective and 5 retrospective). ß3 agonists led to improvements in both urodynamics parameters and self-reported outcomes such as incontinence. Commonly reported side effects were headaches (3%‒5.9%), constipation (3.5%‒5.7%), rhinitis/nasopharyngitis (1.7%‒5.8%) and blurred vision (1.7%‒2.9%). Clinically meaningful changes in safety outcomes (blood pressure, heart rate, electrocardiogram-related changes, liver function) were rare. Before and after ß3 agonist use, pooled effect estimates for maximum cystometric capacity for 171 patients were mean difference of +98.84 ml (95% CI 74.72, 122.96); for complete dryness, assessment of 235 patients showed a Peto odds ratio of 8.68 (95% CI 5.22, 14.45). Conclusions: ß3 agonists appear to be a promising, effective and safe alternative/adjunctive therapy in management of pediatric NDO or OAB, with improvements in both objective urodynamics parameters and subjective patient-reported outcomes following their use.